2016
DOI: 10.1093/jxb/erw324
|View full text |Cite
|
Sign up to set email alerts
|

Plastidic phosphoglucomutase and ADP-glucose pyrophosphorylase mutants impair starch synthesis in rice pollen grains and cause male sterility

Abstract: HighlightAnalysis of rice plastidic phosphoglucomutase and ADP-glucose pyrophosphorylase mutants reveals that starch synthesis in pollen grains requires the production of glucose-1-P and ADP-glucose in the plastids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 77 publications
3
63
0
Order By: Relevance
“…The gene was broadly expressed in all tissues, especially in immature cob and early stage of seed development (Walley et al, 2016). It was found that the plastidic phosphoglucomutase expression was up-regulated when starch began to accumulate, while its mutant impaired starch synthesis in rice pollen grains and caused male sterility (Lee et al, 2016). GRMZM2G069008 encodes a Nudix hydrolase that is widely distributed in dicots and monocots.…”
Section: Functional Annotation For Candidate Genesmentioning
confidence: 99%
“…The gene was broadly expressed in all tissues, especially in immature cob and early stage of seed development (Walley et al, 2016). It was found that the plastidic phosphoglucomutase expression was up-regulated when starch began to accumulate, while its mutant impaired starch synthesis in rice pollen grains and caused male sterility (Lee et al, 2016). GRMZM2G069008 encodes a Nudix hydrolase that is widely distributed in dicots and monocots.…”
Section: Functional Annotation For Candidate Genesmentioning
confidence: 99%
“…For example, FLOURY ENDOSPERM4 (FLO4), encoding a pyruvate orthophosphate dikinase (PPDK; EC 2.7.9.1), was shown to regulate carbon flow from starch and lipid biosynthesis during seeding stage (Kang et al, 2005). Some other factors such as flo2, flo6, flo7, OsbZIP58, OsBT1 (ADP-glucose transporter), RPBF (rice P-box binding factor), OspPGM (plastidic phosphor-glucomutase) and RSR1 (rice starch regulator1) have also been shown to influence starch synthesis and endosperm development in rice (Fu and Xue, 2010;Lee et al, 2016;Li et al, 2017;Peng et al, 2014;She et al, 2010;Wang et al, 2013;Yamamoto et al, 2006;. Mutants of SUBSTANDARD STARCH GRAIN4 (SSG4) and SSG6 show enlarged starch grains (SGs) in the rice endosperm (Matsushima et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Lack or reduced activity of PGM has been attributed to impaired plant growth and development. 21,22 In addition, PGM along with glucose-6phosphate dehydrogenase (G6PDH) is crucial for the generation of energy and formation of nicotinamide adenine dinucleotide phosphate (NADPH), a reducing agent with a vital role in biological reactions. PGM is also an essential enzyme with major implications in metabolic pathways.…”
mentioning
confidence: 99%